Methodologic Considerations for Epigenomic Investigation of Preterm Birth in African American Women. (January 2022) - Nowak, Alexandra L.; Giurgescu, Carmen; Ford, Jodi L.; Mackos, Amy; Ohm, Joyce; Tan, Alai; Pietrzak, Maciej; Anderson, Cindy M.
Epigenetic modifications are chemical changes that can modify gene expression without changing the sequence of the gene. These modifications are potentially identifiable and reversible, making the epigenome an important area of research for discovering biomarkers to identify those who may be at risk and providing therapeutic interventions to prevent adverse health outcomes. African Americans bear a disproportionate risk of adverse health outcomes (e.g., hypertension, cancer). Indeed, African American women experience preterm birth (PTB; <37 completed weeks gestation) at more than twice the rate of non-Hispanic White women. Research suggests that environmental influences may play a significant role in PTB outcomes for this population. However, the biological pathways by which these influences contribute to PTB are poorly understood. This paper describes research methods and ethical considerations for the collection and analysis of biological samples based on our study examining the epigenetic regulation of stress pathways in PTB in pregnant African American women.